Strategi Penguatan Akhlakul Karimah Dalam Mencegah Radikalisme Di Pondok Pesantren Hidayatul Mubtadiin Desa Sidoharjo Kecamatan Jati Agung Kabupaten Lampung Selatan - Puspitasari, Riska; Hasan, Mustaqim; Nugraha, Hendika Adi (Penerbit Widina, Widina Media Utama, 2026)
The main objective of this study is to analyze strategies for strengthening moral values as a preventative measure against radicalism at the Hidayatul Mubtadiin Islamic Boarding School. This study used a qualitative approach with a case study design to explore strategies for strengthening moral values as a preventative measure against radicalism at the Hidayatul Mubtadiin Islamic Boarding School in South Lampung. Subjects included the boarding school leadership, teachers, students, and parents involved in the instilling of moral values. Data were collected through participant observation, in-depth interviews, and documentation of Islamic boarding school activities. Thematic analysis was used to identify patterns, themes, and relationships between strengthening moral values and preventing radicalism. Data validity was maintained through triangulation of sources, techniques, and participants. This methodology emphasized both theoretical and practical aspects, so that the research results provide an empirical contribution to the development of character education-based preventive strategies that are applicable and contextual in Islamic boarding schools. The results of this study indicate that strategies for strengthening moral values as a preventative measure against radicalism at the Hidayatul Mubtadiin Islamic Boarding School. Findings indicate that cultivating moral values through daily activities, such as congregational prayer, Quran recitation, and social participation, fosters ethical awareness and tolerance among students. The role of teachers and mentors as moral role models has been shown to motivate students to emulate positive behavior and avoid the influence of extreme ideologies. Furthermore, active leadership oversight through monitoring, personal guidance, and religious counseling enables early detection of potential radicalism and strengthens the internalization of noble morals. This integrative strategy confirms that religious practice, social interaction, and moral leadership simultaneously shape the character of students who are resilient, tolerant, and critical of the influence of radicalism, providing a new empirical contribution to the literature on character education and radicalism prevention.ABSTRAKTujuan utama penelitian ini adalah menganalisis strategi penguatan akhlakul karimah sebagai upaya preventif terhadap radikalisme di Pondok Pesantren Hidayatul Mubtadiin. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus untuk mengeksplorasi strategi penguatan akhlakul karimah sebagai upaya pencegahan radikalisme di Pondok Pesantren Hidayatul Mubtadiin, Lampung Selatan. Subjek penelitian meliputi pimpinan pesantren, guru, santri, dan orang tua yang terlibat dalam pembiasaan nilai moral. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi kegiatan pesantren. Analisis dilakukan menggunakan teknik analisis tematik untuk menemukan pola, tema, dan hubungan antara penguatan akhlakul karimah dan pencegahan radikalisme. Validitas data dijaga melalui triangulasi sumber, teknik, dan anggota. Metodologi ini menekankan aspek teoritis dan praktis, sehingga hasil penelitian memberikan kontribusi empiris bagi pengembangan strategi preventif berbasis pendidikan karakter yang aplikatif dan kontekstual di lingkungan pesantren. Hasil Penelitian ini menunjukkan bahwa strategi penguatan akhlakul karimah sebagai upaya pencegahan radikalisme di Pondok Pesantren Hidayatul Mubtadiin. Temuan menunjukkan bahwa pembiasaan nilai moral melalui kegiatan harian, seperti shalat berjamaah, tadarus, dan partisipasi sosial, menumbuhkan kesadaran etis dan toleransi antar-santri. Peran guru dan pembina sebagai teladan moral terbukti memotivasi santri meneladani perilaku positif dan menjauhi pengaruh ideologi ekstrem. Selain itu, pengawasan aktif pimpinan melalui monitoring, bimbingan pribadi, dan konseling religius memungkinkan deteksi dini terhadap potensi radikalisme, sekaligus memperkuat internalisasi akhlakul karimah. Strategi integratif ini menegaskan bahwa praktik religius, interaksi sosial, dan kepemimpinan moral secara simultan membentuk karakter santri yang resilien, toleran, dan kritis terhadap pengaruh radikalisme, memberikan kontribusi empiris baru bagi literatur pendidikan karakter dan pencegahan radikalisme.